(untitled) (Bangladesh Journal of Medical Science, 2010)
Training of medical professionals being carried out since centuries, where quality of physician depends upon the quality and accreditation of the training system in place. Quality is the means through which an institution can guarantee, with confidence and certainty that the standards of its educational objectives maintained and enhanced. Quality in higher education is a dynamic process which is the outcome of interaction of multiple factors that determine the state of equilibrium reached at various levels. These include, inter alia, leadership, quality of faculty, quality of students, infrastructure, facilities, research and learning environment, governance, strategic planning, assessment procedures, market forces and several other factors depending upon the type, nature and level of educational processes. Quality Medical Education is a comprehensive concept, which consists of a number of ideas and systematic processes. The basic requirements of Quality Medical Education include a well-planned system of education aimed at achieving the goals and objectives set for it and a comprehensive quality infrastructure for the productive implementation and systematic evaluation of that system. In essence Medical Education has to be of the highest quality to produce doctors capable of giving the highest quality of medical care by not only satisfying the consumers i.e. patients, their families, community and employers but offering a service better than their expectations. Such education will need to adopt more than what is called al Quality culture in the institution. Keywords: Quality control; quality assurance; medical education; accreditation; Ihsan. DOI: 10.3329/bjms.v9i3.6465 Bangladesh Journal of Medical Science Vol.09 No.3 July 2010, pp.116-123